Fish Passage Facilities Design Parameters for Merrimack River Dams: Essex Dam, Lawrence, Massachusetts and Pawtucket Dam, Lowell, Massachusetts - Dalley, P J (ScholarWorks@UMass Amherst, 1975)
None supplied. From introduction: The purpose of this series of reports is to provide guidelines and engineering design parameters for fish passage facilities required to pass substantial numbers of anadromous fish over dams on the Merrimack River Basin. American shad and Atlantic salmon are the main species considered for restoration. Upstream migrant facilities considered for use at the various dams on the Merrimack River Basin include fishways, atmospheric fish locks, fish elevators, and barrier dams. The size, type, and location of fish passage facilities proposed in this report are for guideline purposes only. Those facilities used in the final design will be based on detailed engineering and cost studies made by the respective dam owners and their design engineers working in cooperation with the Technical Committee for Fisheries Management of the Merrimack River Basin.